Radioisotopic labeling of human papovavirus (BK) by iodination and reductive alkylation. - Wright, P J (1976)
Purified virions of the GS strain of the BK group of human papovaviruses were labeled with 125I using chloramine T or lactoperoxidase or with tritium using sodium borohydride. All viral polypeptides were labeled. Tryptic digests of iodinated VP1 were analyzed.